Contact tracing of healthcare workers exposed to COVID-19 infection in a tertiary-care hospital: Containing the contagion - Sarit Sharma; Vikas Gupta; Ashvind Bawa; Ajay Kumar; Puneet Aulakh Pooni; Parshotam Lal Gautam; Ashwani Kumar Chaudhary; Rajoo Singh Chhina (Wolters Kluwer Medknow Publications, 2023)
Introduction: Healthcare workers (HCWs) are at higher risk of getting infected with COVID-19 infection due to their close proximity to COVID-19-positive patients. We studied the risk stratification and positivity rate in HCWs at risk of getting COVID-19 infection as well as the possible factors responsible for their being at risk of COVID-19 infection during the study period. Material and Methods: This prospective study was conducted after approval by the institutional ethics committee. The data regarding demographic variables, risk stratification, COVID-19 (reverse-transcription polymerase chain reaction) report, and possible sources of exposure for HCWs were recorded in a proforma by personal/telephonic interviews as well as from hospital records from March 2020 to June 2021. The data generated were entered into Microsoft Excel® software and analyzed using percentages, proportions, and Chi-square tests for qualitative variables. Results: COVID-19 infection's positivity rate was 19.5% among high-risk and 0.6% among low-risk HCW contacts. HCWs working in non-COVID-19 areas (67.9%) were more at risk than those working in COVID-19 areas (32.1%). In contrast, the COVID-19 positivity rate was significantly higher among high-risk contact HCWs from COVID-19 areas (34.2%) than in non-COVID-19 areas (12.6%). The maximum COVID-19 positivity rate was seen in high-risk contacts with body fluid exposure (21%), performing aerosol-generating procedures (20%), and close exposure in operation theaters (18%). Conclusions: Risk stratification is an important tool to contain infection among HCWs who had unprotected close contact with a COVID-19-positive case. With appropriate contact tracing, we were able to avoid over- and under-quarantine, save many man-hours as well as contain the spread of infection. HCWs should not only wear appropriate personal protective equipment (PPE) during work hours but should also practice mask-wearing and social distancing while they are in the community.